South American and Antarctic Continental Cenozoic Birds: Paleobiogeographic affinities and disparities - Tambussi, Claudia Patricia; Degrange, Federico Javier
Several advances have been made on the understanding of the biotic and environmental history of South America and Antarctica including the discovery of additional fossil sites coupled with progress from multidisciplinary analyses encompassing tectonic, isotopic, and radiochemical dating and molecular studies in modern forms. This also changed the knowledge about birds. Characters of the South American (SAn) avian fossil record are: (1) presence of taxa with uncertain affinities and absence of Passeriformes during the Paleogene; (2) progressive and accelerated increase of species starting at the Neogene (Miocene); (3) dispersal of important extinct lineages (e.g., Phorusrhacidae, Teratornithidae) to North America after the connection between both Americas; (4) scarce endemic species that are members of clades with major diversification during the Neogene (e.g., Cariamiformes) or that inhabit mainly in the southern hemisphere (e.g., Anhingidae); (5) highly diverse living groups with limited (e.g., Passeriformes) or no (e.g., Apodiformes) fossil record of which stem-groups are registered in Europe; (6) absence of the most extant SAn bird lineages; (7) predominance of the zoophagous birds ([60 %) in all the associations (13) under scrutiny. Changes in diversity of the SAn birds during the Cenozoic could have been the result of the action of different processes (dispersal, vicariance, extirpations, or extinctions) that affect groups in different ways. Fil: Tambussi, Claudia Patricia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Degrange, Federico Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. ...